BAKTERIOSIN ASAL BAKTERI ASAM LAKTAT SEBAGAI BIOPRESERVATIF PANGAN - -, Hafsan (Fakultas Sains dan Teknologi UIN ALauddin, 2014)
Lactic Acid Bacteria origin Bacteriocins are protein substances that generally have small molecular weight as well as bactericidal activity that has the potential to be used as biopreservatif to prevent spoilage, and inhibit the growth of pathogenic bacteria in food. Bacteriocins as biopreservatif mechanism is to form holes in the membrane. Effect of cytoplasmic hole formation is the presence of bacteriocins impact that caused the membrane potential gradient changes and the release of intracellular molecules and influx of extracellular substance. The effect causes inhibited cell growth and cell death in the producing process that is sensitive to bacteriocins. Bacteriocins will work actively in the pH range 5-8, and are stable on heating to 80 Â° C and the activity was marred by the presence of proteolytic enzymes. Advantages of the use of antimicrobial bacteriocins in mengeliminer ability of pathogenic microbes and food spoilage origin of milk and meat. Application as a therapeutic substance is possible due to its antimicrobial characteristics that are not toxic, capable of inhibiting the low levels and produced by bacteria belonging to GRAS (Generally recognised as safe) which microbes are not a health risk.